Metodología para la inspección estructural en los procesos de mampostería en los proyectos de la empresa Miguel Cruz y Asoc. LTDA. - Guasch-García, Alejandro (Instituto Tecnológico de Costa Rica, 2017)
The report presented below describes the processes carried out to carry out an adequate inspection in the projects designed by the consulting firm Miguel Cruz y Asociados, with the objective of implementing a methodology of optimization of the inspection process by means of digital tools, to Reaching this objective was necessary a study of the national and international regulations applicable to Costa Rica, the development of a structural design based on masonry, the preparation of checklists and finally validated in the field. The results of the research were also complemented with the experience of the professionals in charge of the company, with which the tool of the lists was developed and a manual of use of the same ones, besides in the design it was contrasted with the existing regulations and It was understood how a work must comply to conform to what is established as a design, finally a field validation was established which helped to understand that the constructors perform with the designs and problems present in the execution process.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Inspección; Mampostería; Verificación; Optimización; Manual